THE EFFECT OF THE READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE (RADEC) LEARNING MODEL ON STUDENTS' CHEMICAL LITERACY SKILLS IN THE INDEPENDENT CURRICULUM - Aufa Rofiki Lubis, Maulida; Alvina, Sirry; Muliaman, Agus; Rezkia Lukman, Isna; Fakhrah, Fakhrah (Chimica Didactica Acta, 2024)
This research aims to determine the influence of the Read, Answer, Discuss, Explain, and Create (RADEC) model on the chemical literacy abilities of class XI students at SMA Negeri 7 Lhokseumawe through aspects of chemical literacy, namely aspects of context, knowledge, and competence. This research is Pre-Experimental Design research, carried out in the odd semester of the 2023/2024 academic year at SMA Negeri 7 Lhokseumawe. The subjects in this study consisted of 2 classes that took cross-interest chemistry lessons, namely classes XI-1 and XI-2, with 55 students. Sampling was carried out by purposive sampling. The data collection techniques and instruments used in this research were essay questions in the form of stories or literacy, totaling nine questions about reaction rate. The research results show that the t-test data on students' chemical literacy test learning outcomes has a sig. value. (2-tailed) 0.000 0.05, so H0 is rejected, and Ha is accepted. The conclusion is that the RADEC learning model influences the scientific literacy abilities of class XI students at SMAN 7 Lhokseumawe on the reaction rate material. The average value of the students' chemical literacy aspects is that the average value of the context aspect in the experimental class is 79.01, the knowledge aspect is 87.65, and the competency aspect is 60.49. The average value of the context aspect in the control class is 69.04, the knowledge aspect is 35.11, and the competency aspect is 45.83. The influence of chemical literacy abilities can be seen from the average value of students who use the RADEC learning model 76, with the good criterion being higher than students who use the conventional learning model, which is 50 with sufficient criteria.